Role of Electrolytes in the Stability and Safety of Lithium Titanate-Based Batteries - Ghosh, Arunabh; Ghamouss, Fouad (Frontiers in Materials, 2020)
Lithium titanate (Li4Ti5O12, LTO) has emerged as an alternative anode material for rechargeable lithium-ion batteries with the promises of long cycle life, superior safety, better low-temperature performance, and higher power density compared to their graphite-based counterparts. LTO, being a “zero-strain” material, shows almost no volume change (<1%) during lithium insertion/extraction and hence offers excellent cycling stability (over 20,000 cycles). LTO anodes were initially popular with the belief that these anodes’ electrolyte-interfaces were free of any solid electrolyte interphase (SEI) layers. However, that was found to be not accurate. Rather recent studies have reported different types of deposits and layer formations on the surface of LTOs, and therefore this unexplored area got serious attention from the past few years and emerged as an important future research direction. However, these anodes, being very active catalysts, suffer from severe unwanted reactions with electrolytes, and problems like gas evolution and associated swelling of the battery pack happen. On the other hand, electrolytes were found to be one of the primary sources of these problems, as they are also reactive with both anode and cathodes, and this creates a severe stability and safety concern. The presence of moisture within the system, decomposition of the electrolyte solvents and solutes, high catalytic activities of the anode, are among the possible reasons behind the instability of an LTO based battery. Developing an appropriate chemical composition of the electrolyte, and/or modification of the electrode/electrolyte interface can provide prevention from these issues.